2021
DOI: 10.3390/molecules26082178
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Biological Activity of Camellia Species

Abstract: Medicinal plants have been used since antiquity to cure illnesses and injuries. In the last few decades, natural compounds extracted from plants have garnered the attention of scientists and the Camellia species are no exception. Several species and cultivars are widespread in Asia, namely in China, Japan, Vietnam and India, being also identified in western countries like Portugal. Tea and oil are the most valuable and appreciated Camellia subproducts extracted from Camellia sinensis and Camellia oleifera, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 122 publications
2
31
0
2
Order By: Relevance
“…There were critical differences among all results of each tried bacteria organisms treated with the concentrates E1, E2, and E3 as control. Also, huge significant differences were founded at all tried microbes towards treatments E1, E2, and E3, Table (3 There were several works reach agreement with present study thus results by Radji et al, (2013) concluded that leave quotation for Camellia might be suitable in opposing initial drug resistance caused by MRSA and Pseudomonas aeruginosa, other investigation by Teixeira and Sousa, (2021), give highpoints for camellia spp. As a featured that has antimicrobial (antibacterial, antifungal antiviral) and antitumoral action and just like a massive basis of polyphenols like the catechins.…”
Section: Determine the Micsupporting
confidence: 84%
See 1 more Smart Citation
“…There were critical differences among all results of each tried bacteria organisms treated with the concentrates E1, E2, and E3 as control. Also, huge significant differences were founded at all tried microbes towards treatments E1, E2, and E3, Table (3 There were several works reach agreement with present study thus results by Radji et al, (2013) concluded that leave quotation for Camellia might be suitable in opposing initial drug resistance caused by MRSA and Pseudomonas aeruginosa, other investigation by Teixeira and Sousa, (2021), give highpoints for camellia spp. As a featured that has antimicrobial (antibacterial, antifungal antiviral) and antitumoral action and just like a massive basis of polyphenols like the catechins.…”
Section: Determine the Micsupporting
confidence: 84%
“…polyphenols of green tea underpinning properties and natural movement (Teixeira and Sousa, 2021). Moringa oleifera and Moringa stenopetala are underutilized types of tropical trees that may assume a significant part in dietary expansion and add to the mitigation of stowed away yearning in less created tropical and subtropical nations, numerous investigations propose that Moringa spp.…”
Section: Research Articlementioning
confidence: 99%
“…In general, the greater the reduction potential, the faster the reaction rate and the production of smaller nanoparticles. The latest review of Teixeira et al [ 70 ] also highlighted the extraordinary effectiveness of Camellia species as natural antioxidants. It should be emphasized that the impressive antioxidant potency of Camellia extract is caused by the polyphenolic compounds, mainly (–)-epigallocatechin-3-gallate, (–)-epigallocatechin, (–)-epicatechin-3-gallate, and (–)-epicatechin, owing to the presence of multiple OH functional groups in their structures.…”
Section: Discussionmentioning
confidence: 99%
“…Tea polyphenols can significantly inhibit the growth of E. coli. TPs can destroy the cell structure of E. coli, increase the permeability of the cell wall, and reduce the number of E. coli [87].…”
Section: Regulation Of Tea Polyphenols On Intestinal Flora-effective Prevention Of Mental Diseasesmentioning
confidence: 99%